Media Framing of Identity Politics through Prejudice and Stereotype Towards the 2024 Election - Semuel Akihary; Rustono Farady Marta; Hana Panggabean (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
This research discusses identity politics through prejudice and stereotype toward the 2024 presidential election. Identity politics refers to the way politics works in determining and classifying identities. In its development, especially in the last few elections, identity politics is full of harmful content that divides various elements of society. This study aims to analyze the media framing raised in three perspectives of online media, namely, Mediaindonesia.com, Detik.com, and Kompas.com. This study used a qualitative method using Pan & Kosicki’s framing theory. The study results show that Mediaindonesia.com's news content aims to provide normative justification while safeguarding the integrity of the NasDem party as a